Side-Chain Polyimides as Binder Polymers for Photolithographic Patterning of a Black Pixel Define Layer for Organic Light Emitting Diode - Genggongwo Shi; Sung Hoon Park; Jeseob Kim; Minji Kim; Lee Soon Park (International Journal of Polymer Science)
A pixel define layer (PDL) in an organic light emitting diode (OLED) is patterned using a photolithographic process before the deposition of organic layers on top of ITO anode. If the patterning of PDL on OLED panels can be achieved using a black photoresist, the patterning of black matrix (BM) on top of PDL patterns can be omitted by reducing the reflection of ambient light from OLED panels. In this study, we synthesized a series of side-chain-type polyimides as binder polymers of black photoresists and investigated the potential of using the black photoresist for the fine patterning of black PDL on OLED panels.